The Effect of PhET Interactive Simulation Media Based on the STEM Approach on Students’ Learning Outcomes on Acid–Base Material in Grade XI Senior High School - Enjelina Sihombing; Marini Damanik (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
The Effect of PhET Interactive Simulation Media Based on the STEM Approach on Students’ Learning Outcomes on Acid–Base Material in Grade XI Senior High School. This study aimed to determine the effect of PhET Interactive Simulation media based on the STEM approach on students’ learning outcomes and the improvement of learning outcomes on acid–base material. This research was a quasi-experimental study using a pretest– posttest control group design. The population consisted of all students of class XI MIPA at SMA Negeri 4 Medan. The sample was selected using purposive sampling, consisting of two classes with a total of 68 students, namely the experimental class and the control class. Data were obtained through a learning outcomes test and analyzed using a normality test, a homogeneity test, an independent sample t-test, and N-Gain analysis. The results showed that the average posttest score of the experimental class was 85.06, while the control class was 77.88. The hypothesis test showed a significance value of 0.000 < 0.05, indicating that the use of PhET Interactive Simulation media based on the STEM approach has a significant effect on students’ learning outcomes on acid–base material. The N-Gain analysis also showed that the experimental class achieved a high category improvement, while the control class was in the medium category.